Experimental study of phase relations in the U–Ti–Al ternary system. (February 2015) - Moussa, Chantal; Pasturel, Mathieu; Stepnik, Bertrand; Tougait, Olivier
Abstract: The phase relations in the ternary U–Ti–Al system were established for the whole concentration range for two temperatures, 923 K and 1123 K. They were derived from quenched samples annealed at 1123 K for about 500 h and at 923 K for about 720 h using X-ray powder diffraction, scanning electron microscopy and energy dispersive spectroscopic analysis. Only one ternary phase, the Al-rich compound, UTi2 Al20, was found. It forms by a peritectic reaction at 1365(5) K, and remains stable at least down to 923 K. Based on single-crystal structure refinements, it was confirmed that it adopts the CeCr2 Al20 structure type (cubic, F m 3 ¯ d, n°227) with lattice parameter at room temperature, a = 14.634(1) Å. Unlike most of the isotypic aluminides, UTi2 Al20 should be regarded as a line compound. At 1123 K, the isothermal section is characterized by the extended homogeneity ranges due to mutual exchange between U and Ti and between Ti and Al in the unary phases, whereas at 923 K, the mutual solubility between U and Ti was found null. Regarding the binary phases, only in the Laves phase, UAl2 (cubic-C15, MgCu2 -type) such solubilities were observed with limits of about 2 at% of U by Ti and 5.5 at% of Al by Ti, at 1123 K. For the other binary compounds, the solubility of the third component was found negligible at both temperatures. Highlights: Isothermal sections of the U–Ti–Al system were investigated for 923 K and 1123 K. The crystallographic properties of the equilibrium phases were checked. The microstructure of quenched alloys was discussed. The existence and the identification of any intermediate phases were carried out. The formation reaction of UTi2Al20 was determined.